(untitled) (International Journal of Banking and Finance, 2024)
Trading is a business, not an investment. Traders focus on minor to secondary trends, while investors focus on the primary trend. The trading timeframe is crucial in technical analysis. As such a trader who trades with a minor trend timeframe, must have a trading strategy. We aim to examine the impact of the moving averages double crossover strategy on traders’ profit factor based on minor and secondary trend timeframes before, during and after the lockdown periods. Dow Theory was adopted for this study as a trend should be in effect until it gives a definite signal for a reversal. Data was collected from the Nasdaq Composite Index for a five-year period, from 2018 to 2022. During this time frame, the required data for the study was obtained at the point of the golden crossover and exiting at the dead crossover, in which 2018 to 2019 was the period before the lockdown, 2020 to 2021 was the period during lockdown, and 2022 was the year after lockdown. By using trading profits and loss for both longs and shorts, we back tested three strategies of double crossover moving averages that were as follows: i) EMA5 crossover EMA10, ii) EMA5 crossover EMA20 and iii) EMA20 crossover EMA50. A non-parametric analysis of independent samples was used. The result shows that there was a significant difference among those three strategies before the lockdown period, but no significant difference during and after the lockdown period.